Juvenile glaucoma: A chance encounter in the consultation - Ibanez Navarro Alberto; Tobajas Calvo Julián; Villafranca Serrano Sofía; Rodríguez Pineda Adela; Salas García Iván José (The Pan-American Journal of Ophthalmology, 2020)
Juvenile glaucoma is a rare entity, starting below the age of 35–40 years, which is discovered as a casual finding in reviews or consultations for other reasons. It is inherited from autosomal dominant penetrance. It can lead to a loss of visual acuity. The treatment is similar to conventional glaucoma, although its control, when diagnosed, is usually late and usually leads to more complex management. The differential diagnosis of glaucoma by steroids, trauma, inflammatory, or congenital late diagnosis must be made. The main difference with other types of glaucoma is that it is generally asymptomatic, and there is no corneal edema or Haag striae. Surgery is an alternative when drug treatment fails. Through a real case, we want to introduce and develop this ophthalmological pathology. This is a 25-year-old male with a history of myopia, who at a casual check-in an optician's shop is found to have increased intraocular pressure (IOP). In the campimetry was seen a ring scotoma (right eye) and an arciform scotoma (left eye [LE]). Distant vision was preserved. In optical coherence tomography there was bilateral decrease of retinal nerve fiber layer thickness , and in the right eye (RE) gonoscopy showed a highly pigmented Grade IV open angle. Initially, pharmacological management was attempted (with carbonic anhydrase inhibitors, beta-blockers and prostaglandin analogs) by achieving it in the LE. However, the RE ended up with a trabeculectomy, obtaining, in the end, a good control of the IOP.